Does p53 Inhibition Suppress Myocardial Ischemia–Reperfusion Injury?. (July 2018) - Yano, Toshiyuki; Abe, Koki; Tanno, Masaya; Miki, Takayuki; Kuno, Atsushi; Miura, Tetsuji; Steenbergen, Charles
P53 is well known as a regulator of apoptosis and autophagy. In addition, a recent study showed that p53 is a modulator of the opening of the mitochondrial permeability transition pore (mPTP), a trigger event of necrosis, but the role of p53 in necrosis induced by myocardial ischemia–reperfusion (I/R) remains unclear. The aim of this study was to determine the role of p53 in acute myocardial I/R injury in perfused mouse hearts. In male C57BL6 mice between 12 and 15 weeks of age, 2 types of p53 inhibitors were used to suppress p53 function during I/R: pifithrin-α, an inhibitor of transcriptional functions of p53, and pifithrin-μ, an inhibitor of p53 translocation from the cytosol to mitochondria. Neither infusion of these inhibitors before ischemia nor infusion for the first 30-minute period of reperfusion reduced infarct size after 20-minute ischemia/120-minute reperfusion. Infarct sizes were similar in p53 heterozygous knockout mice (p53 +/− ) and wild-type mice (WT), but recovery of rate pressure product (RRP) 120 minutes after reperfusion was higher in p53 +/− than in WT. The protein expression of p53 in WT was negligible under baseline conditions, during ischemia, and at 10 minutes after the start of reperfusion, but it became detectable at 120 minutes after reperfusion. In conclusion, upregulation of p53 during the late phase of reperfusion plays a significant role in contractile dysfunction after reperfusion, although p53 is not involved in cardiomyocyte necrosis during ischemia or in the early phase of reperfusion.